Activation of de novo synthetic pathway of ceramides is responsible for the initiation of hydrogen peroxide induced apoptosis in HI-60 cells - Son, Jung Hyun; Yoo, Hye Hyun; Kim, Dong-Hyun (TAYLOR & FRANCIS INC, 2007)
Sphingolipid metabolites in HL-60 cells were analyzed to gain an understanding of their roles in early events underlying hydrogen peroxide (H2O2)-induced apoptosis. Incubation of cells with H2O2 increased the intracellular levels of ceramides and sphinganine, but decreased those of ceramide 1-phosphates (ceramide 1-P) and sphingosine. The levels of sphingomyelins and sphingo- myelinase (SMase) activities were not affected by H2O2 treatment. These results were similar to the profiles induced by daunorubicin, an activator of serine palmitoyl CoA transferase (SPT), suggesting that H2O2 stimulated the de novo synthetic pathway of ceramides. L-cycloserine and fumonisin B, (FBI), specific inhibitors of de novo ceramide biosynthesis, suppressed the elevation of ceramides and sphinganine induced by 112021 which consequently reduced apoptotic cell death. Collectively, these results demonstrated that H2O2 increased the intracellular concentrations of ceramides via activation of a de novo biosynthetic pathway, and the enhanced ceramides might initiate apoptosis in HL-60 cells.
Keywords: STRESS-INDUCED APOPTOSIS; SPHINGOSINE 1-PHOSPHATE; OXIDATIVE STRESS; SPHINGOMYELIN HYDROLYSIS; ENDOTHELIAL-CELLS; LLC-PK1 CELLS; HL-60 CELLS; GENERATION; DEATH; DIFFERENTIATION